The Pre-Dawn of the Three Caverns Thought: An Examination Based on Shangqing taiji yinzhu yujing baojue - Ling Cao (Religions)
The emergence of the “Three Caverns” 三洞 thought was a critical step in the formation of medieval Daoism. It proposed the first viable approach to integrating emerging Daoist scriptural traditions, enabling the creation of the first canonical Daoist catalog, and laying the foundation for the compilation of the Daozang and the establishment of the Ordination Ranks 法位 system. Scholars generally agree that the Shangqing taiji yinzhu yujing baojue 上清太極隱注玉經寶訣 played a significant role in the development of the Three Caverns thought. However, research on the formation of this scripture remains lacking. This study fills this gap by confirming the composition of the scripture through two independent lines of evidence. Then, based on new insights into its composition, this study discusses the historical context of the Three Caverns concept in this scripture and its direct impact on Lu Xiujing 陸修靜 (406–477)’s cataloging work. These discussions illustrate that, when confronted with the challenge posed by the newly composed Shangqing scriptures, the authors of the Shangqing taiji yinzhu yujing baojue employed the integrative approach commonly found in the Ancient Lingbao Scriptures to propose a more inclusive scriptural system. This approach played a crucial role in providing a theoretical foundation for the formation of medieval Daoism.